51.5k views
0 votes
I dont understand this!!! What's the answer?

I dont understand this!!! What's the answer?-example-1

2 Answers

6 votes

To put this into words, the equation is saying that one less than 4x + 3x is equal to 6.

First simplify by combining like terms. We see there is a 4x and 3x, which means that they are compatible with each other. The equation will then look like
7x - 1 = 6. If one less than 7x is 6, then this can also mean one more than 6 is equal to 7x. So add 1 to both sides:
7x - (-1 + 1) = (6 + 1)

-->
7x = 7, which means that x = 1.

Checking your work:

Now that we know the value of x, substitute that for x in the equation like this:


4(1) + 3(1) - 1 = 6

-->
4 + 3 - 1 = 6

--->
7 - 1 = 6

So you know it's true that x = 1. Hope this was helpful.

User Jota
by
6.4k points
5 votes

The answer is 1.

4x + 3x - 1 = 6

7x - 1 = 6 -Add the like terms

7x - 1 + 1 = 6 + 1 -Add 1 to both sides to 7x by itself

7x = 7

7x / 7 = 7 / 7 -Divide both sides by 7

x = 1

Hope I helped!